Microeconomic theory for the social sciences - Hayashi, Takashi
This textbook covers microeconomic theory at the level of intermediate and advanced undergraduates. It is also intended as an introduction for those with other intellectual and academic backgrounds who may not necessarily agree with mainstream economists but at least are interested knowing how they think and see things. The book provides thorough explanations of definitions and assumptions that the theory is based upon. It provides comprehensive accounts of motivations and reservations behind the theory. As well, it precisely presents the logical process of how the assumptions lead to the conclusion, conveying the intuition and the key of the arguments. An abundance of topics is included here: individual choice, general equilibrium, partial equilibrium, game theory, imperfect competition, transaction under incomplete information, market failures, welfare economics, social choice and mechanism design. The book is a valuable resource for any reader studying or simply interested in microeconomic theory.